Proteasome inhibitors in medullary thyroid carcinoma: time to restart with clinical trials? - Fanciulli, Giuseppe; Modica, Roberta; La Salvia, Anna; Grossrubatscher, Erika Maria; Florio, Tullio; Ferraù, Francesco; Veresani, Alessandro; Russo, Flaminia; Colao, Annamaria; Faggiano, Antongiulio (Frontiers in Endocrinology, 2023)
Introduction Medullary thyroid cancer (MTC) is a rare thyroid tumour whose management in advanced stages is challenging, despite effective therapeutic options having expanded in recent years. Proteasome inhibitors (PrIn) have shown the ability to improve patient outcomes, including survival and quality of life, in several malignancies, due to their ability to impair cell proliferation and cause apoptosis through the inhibition of the proteasome activity. Consequently, these drugs could represent a useful tool, alone or in combination with other treatments, in MTC patients. Aim of the study This review aims to summarize the available in vitro and in vivo data about the role of PrIn in MTC. Materials and methods We performed an extensive search for relevant data sources, including full-published articles in international online databases (PubMed, Web of Science, Scopus), preliminary reports in selected international meeting abstract repositories, and short articles published as supplements of international meetings, by using the following terms: medullary thyroid carcinoma, proteasome inhibitors, bortezomib, carfilzomib, ixazomib, delanzomib, marizomib, oprozomib, and MG132. Additionally, we conducted with the same keywords, an in-depth search in registered clinical trials repositories. Results Our search revealed in vitro studies in human and murine MTC cell lines, based on the use of PrIns, both alone and in combination with other anticancer drugs, and two pertinent clinical trials. Conclusion We found a strong discrepancy between the evidence of PrIns effects in preclinical studies, and the scarcity or early interruption of clinical trials. We might speculate that difficulties in enrolling patients, as happens in other rare diseases, may have discouraged trials’ implementation in favor of drugs already approved for MTC. However, given the concrete improvement in the comprehension of the molecular basis of PrIn effects in MTC, new clinical trials with accurate inclusion criteria of enrollment might be warranted, in order to ascertain whether this treatment, alone or in combination with other drugs, could indeed represent an option to enhance the therapeutic response, and to ultimately improve patients’ outcome and survival.